Quality of communication between teachers and students in boarding schools - Milanović, Nedeljko M. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2020)
This paper presents the results of an empirical research aimed at understanding students’ attitudes toward the communication they have with a teacher in a boarding school. The study was conducted on a sample of 67 subjects, 36 female and 31 male. For the purposes of this research, a descriptive method - a survey technique - was used. The analyzed results of the research show that the majority of students feel comfortable and relaxed in communication with the teacher. According to the students, communication in boarding schools can be improved by organizing workshops on verbal and non-verbal communication, greater commitment of teachers to communication with students and having more time and patience to listen to students. The results of the study show that students believe that teachers possess valid verbal and non-verbal communication skills and that teachers have more democratic communication than autocratic ones. To make the life and daily functioning of the students in the boarding school positive and effective, it is also necessary that the communication on the teacher-student relationship be of a good quality, healthy and successful.